CATHODOLUMINESCENCE AND RAMAN SPECTROSCOPY AS A BASIS FOR THE SELECTION OF REFERENCE SAMPLES FOR LA-ICP-MS ANALYSIS OF ZIRCON - S. L. Votyakov; M. V. Chervyakovskaya; Yu. V. Shchapova; E. A. Pankrushina; G. B. Mikhalevsky; V. S. Chervyakovsky (Геодинамика и тектонофизика, 2022)
In order to develop express methods for the quantitative assessment of properties and the selection of reference samples close to investigated sample, to ensure similar conditions for the evaporation of substances and parameters of fractionation of trace elements in LA-ICP-MS, a comparative analysis of the U-Pb isotopic composition, Raman and cathodoluminescent spectra of zircon GJ-1, Plesovice, 91500, Temora-2, Mud Tank reference samples has been performed. Variations in the position and width of the full width at half maximum (FWHM) mode of asymmetric stretching vibrations ν3(SiO4) B1g, as well as the values of the accumulated autoradiation dose Dα and the equivalent dose Dαed have been analyzed. It has been shown that in the series Mud Tank→91500→Temora-2→GJ-1→Plesovice, an increase in the degree of autoradiation damage is recorded: the first three samples are slightly damaged; Plesovice is a moderately damaged difference. The analyzed reference samples can be correctly used for LA-ICP-MS analysis of samples of weakly damaged zircons from magmatites, as well as fragments (zones) of zircon grains from metamorphic rocks of weak and medium degree of structural damage. For the first time, using a Jeol JSM6390LV SEM equipped with a Horiba H-CLUE iHR500 attachment, cathodoluminescence spectra of zircon reference samples were obtained in the 200–800 nm range. It has been found that the integral luminescence brightness varies for samples by more than an order of magnitude; the spectra are of a complex superposition nature; their decomposition into elementary components is ambiguous; a large number of components is detected, which are combined into three main Аi–Вi–Сi groups of broad bands in the near-ultraviolet (UV), blue-green and yellow regions with Emax=4.3–5.0, 2.6–3.5, and 2.1–2.3 eV, respectively. For the first time, it wasproposed to use a triple Аi–Вi–Сi diagram to discriminate zircons by their luminescent properties. It has been found that the position of zircon standards on it significantly differs, which is proposed to be used as a basis for an express assessment of their properties and selection. A comparative analysis was performed on the U-Pb isotopic composition, discordance of age determinations, features of Raman and cathodoluminescence spectra for a large sample of accessory zircon from kimberlites and diamond-bearing placers of Yakutia, as well as metamorphic rocks of the Urals – from granite of the final phase of the Neplyuevsky pluton, high-magnesian diorite massif, from high-pressure garnetites of the Mindyaksky lherzolite massif, from leptinites of the Taldyk block Mugodzhar. The Аi–Вi–Сi diagram is compared with similar data on the cathodoluminescence of the reference samples.